2009
DOI: 10.1002/humu.20922
|View full text |Cite
|
Sign up to set email alerts
|

Penetrance of pulmonary arterial hypertension is modulated by the expression of normalBMPR2allele

Abstract: Familial pulmonary arterial hypertension (FPAH) is a progressive, fatal disease caused by mutations in the bone morphogenetic protein receptor type 2 gene (BMPR2). FPAH is inherited as an autosomal dominant trait and shows incomplete penetrance in that many with BMPR2 mutations do not develop FPAH suggesting a role for, as yet unidentified, modifier genes in disease penetrance. We hypothesized that variable level of expression of the wild type (WT) BMPR2 allele could act as a modifier and influence penetrance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 30 publications
4
91
0
4
Order By: Relevance
“…Nearly 80% of mutation carriers never develop the disease, but they can produce offspring that develop HPAH (11). We used gene expression profiling and layered bioinformatics analyses, including the use of cMap, to identify the cellular pathways involved in HPAH penetrance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 80% of mutation carriers never develop the disease, but they can produce offspring that develop HPAH (11). We used gene expression profiling and layered bioinformatics analyses, including the use of cMap, to identify the cellular pathways involved in HPAH penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the expression of nonmutated wild-type BMPR2 allele transcript may be one molecular mechanism of this observed reduced penetrance; however, it is likely that there are unknown additional factors and pathways that influence disease risk (10,11). Identification of such pathways that differ between affected mutation carriers and unaffected mutation carriers represents a strategy for gaining additional molecular insights into HPAH penetrance and possible discovery of new treatment options.…”
mentioning
confidence: 99%
“…This observation is similar to hereditary predisposition to cancer, exemplified by the two-hit hypothesis proposed by KNUDSON [28] for tumour suppressor genes, which corresponds to a germ-line loss of function for one allele and a somatic loss of the second allele. In the case of PAH, the second event might be, as well as genetic, either environmental as suggested by somatic chromosomal abnormalities found in the lungs of PAH subjects [29], or epigenetic, potentially leading to decreased expression of the normal BMPR2 allele [30]. …”
Section: Genetics Of Pulmonary Hypertension D Liu Et Almentioning
confidence: 99%
“…Acquired somatic chromosomal abnormalities in the BMPR2 signaling pathway have also been described (6). The low penetrance of pulmonary arterial hypertension (PAH) found in nonaffected family members with a BMPR2 mutation has been attributed to a higher level of BMPR2 expression from the normal allele (7). In addition, patients with IPAH without a BMPR2 mutation or with PAH associated with other conditions have reduced expression of BMPR2 in pulmonary arteries (8).…”
Section: Introductionmentioning
confidence: 99%